2016
DOI: 10.1177/0890117116639569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise-Based Interventions on Neonatal Outcomes

Abstract: Structured physical exercise programs during pregnancy appear to be safe for the neonate, mainly favoring a lower birth weight within normal range. However, more studies are needed to establish recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 57 publications
2
29
0
Order By: Relevance
“…In line with a meta-analysis which focused on antenatal interventions for overweight or obese pregnant women, 44 the present meta-analysis found no significant difference in the risk of gestational hypertension or preeclampsia between the exercise and control groups. Similar to previous studies, 38,39,42,43,45 the current meta-analysis found no difference in the risk of cesarean delivery between the two groups, especially when both overweight and obese pregnant women were involved.…”
Section: Discussionsupporting
confidence: 89%
“…In line with a meta-analysis which focused on antenatal interventions for overweight or obese pregnant women, 44 the present meta-analysis found no significant difference in the risk of gestational hypertension or preeclampsia between the exercise and control groups. Similar to previous studies, 38,39,42,43,45 the current meta-analysis found no difference in the risk of cesarean delivery between the two groups, especially when both overweight and obese pregnant women were involved.…”
Section: Discussionsupporting
confidence: 89%
“…16 The Australian LIMIT RCT 19 also showed that lifestyle interventions addressing diet and exercise, which were similar to those used in the UPBEAT study, had no effect on reducing the proportion of LGA in overweight and obese pregnant women; however, the proportion of infants weighing >4 kg was lower in the women allocated to the intervention group. A recent meta-analysis 55 including 14 RCTs reported that an exercise program during pregnancy was effective at reducing neonatal birthweight, moreover, did not negatively affect gestational age at delivery. Barakat et al 56 showed that a 3 d/wk exercise program with sessions lasting 50-55 minutes from 9-11 gestational weeks until 38-39 weeks was effective in preventing the development of hypertension and reducing the incidence of macrosomia.…”
Section: Reports Of Major Impactmentioning
confidence: 99%
“…[5][6][7][8][9][10] In terms of life style during pregnancy, physical activity (PA) practice has shown beneficial maternal and child health effects. [11][12][13] Current evidence suggests a lower incidence of pregnancy-related complications such as gestational diabetes, preeclampsia, preterm birth and postpartum depression. 14,15 In addition, studies focusing on the neonatal period and child growth have shown a lower incidence of low birthweight, improved child body composition (lower body fat percentage), and a greater ponderal index.…”
mentioning
confidence: 99%